THE INFLUENCE OF PARTICIPATORY LEADERSHIP PRINCIPLES AND ORGANIZATIONAL COMMITMENT TO TEACHER PERFORMANCE SENIOR HIGH SCHOOL - Rosthavita Yolanda ROSYID (Journal of Education and Leadership in Education, 2021)
This study aimed to determine the effect of the principal's participatory leadership and organizational commitment to the teacher performance. The population in this study were all high school teachers in Koja District, North Jakarta. The population chosen was a random sampling technique from 7 schools consisting of 148 teachers. Then calculated using the Slovin formula, 108 teachers were obtained as the research sample. The data collection technique used a questionnaire instrument with a survey method, the instrument was made using a Likert scale model. Then the instrument was calibrated using the item validation test and the reliability coefficient with the Alpha Croanbach formula. The data analysis requirements were tested by normality of Kolmogorov Smirnov (Liliefors). Data analysis using simple regression techniques and linearity test and finally with path analysis. In view of the exploration results, it tends to be presumed that the chief's participatory initiative has a positive and huge impact on educator execution. Authoritative responsibility additionally has a positive and critical impact on educator execution. Lastly there is a critical and positive impact of the central's participatory authority on authoritative responsibility.